Method of process control automation by energy supply a farm from autonomous energy sources - Holyk, O.; Zhesan, R.; Miroshnichenko, M.; Голик, О. П.; Жесан, Р. В.; Мірошніченко, М. С. (Baltija Publishing, 2018)
The proposed method of automation of the process of controlling the power supply of the farm from autonomous sources of energy can greatly simplify the process of selecting power plants and optimal composition of the autonomous energy supply system of the farm Запропонований спосіб автоматизації процесу управління енергозабезпеченням господарства від автономних джерел енергії може значно спростити процес відбору електростанцій та оптимального складу автономної системи енергопостачання фермерського господарства
Keywords: backup power plants; renewable energy sources; резервна електростанція; відновлюване джерело енергії